Paradoxical Reaction to Alprazolam in an Elderly Woman with a History of Anxiety, Mood Disorders, and Hypothyroidism - Daniel Kirkpatrick; Tyler Smith; Mitchell Kerfeld; Taylor Ramsdell; Hasnain Sadiq; Arun Sharma (Case Reports in Psychiatry)
With less than 1% of patients who use benzodiazepines being affected, paradoxical responses to benzodiazepines are rare. In this case report, we outline the course of an 80-year-old female who developed a paradoxical response to benzodiazepines. Significant medical and psychiatric history includes anxiety, mood disorder, hypothyroidism, bilateral mastectomy, goiter removal, and triple bypass. The patient presented with mental status changes, anxiety, motor restlessness, and paranoia. Over time, a temporal relationship between the severity of the patient’s motor agitation and intake of alprazolam was observed. As doses of alprazolam were decreased, her motor agitation became less severe. In addition to motor agitation, the patient also demonstrated increased aggressiveness, a subjective feeling of restlessness, and increased talkativeness. As her dose of alprazolam decreased, many of the patient’s symptoms were observed to decrease. This case report also discusses theories regarding the pathophysiology of paradoxical reactions to benzodiazepines, known risk factors, and appropriate treatment.